Clinical performance of DNA‐based prenatal screening using single‐nucleotide polymorphisms approach in Thai women with singleton pregnancy. Issue 7 (24th April 2020) - Panchalee, Tachjaree; Poungvarin, Naravat; Amornrit, Warisa; Pooliam, Julaporn; Taluengjit, Pattarawalai; Wataganara, Tuangsit
Abstract: Background: To review the performance of noninvasive prenatal screening (NIPS) using targeted single‐nucleotide polymorphisms (SNPs) approach in mixed‐risk Thai women. Methods: Retrospective analysis of data for detection of trisomy 21 (T21), 18 (T18), 13 (T13), monosomy X (XO), other sex chromosome aneuploidies (SCA), and triploidy/vanishing twins (VT) from a single commercial laboratory. Results: Mean (± SD ) gestational age and maternal weight were 13.2 (±2.1) weeks and 125.7 (±22.4) pounds, respectively ( n = 8, 572). From 462/8, 572 (5.4%) no‐calls; 1/462 (0.2%) was uninformative SNPs, and 1/462 chose amniocentesis. Redraw settled 323/460 (70%) samples with low fetal fraction (FF); and 8, 434/8, 572 (98.4%) were finally reportable, with 131 high risks (1.6%). The median (min‐max) FF of reportable ( n = 8, 434) and unreportable samples ( n = 137) samples were 10.5% (2.6–37.9) and 3.8% (1–14.1), respectively ( p < .05). Fetal karyotypes were available in 106/131 (80.9%) and 52/138 (37.7%) high risk and repeated no‐calls, respectively. The positive predictive values (PPVs) for T21 ( n = 47), T18 ( n = 15), T13 ( n = 7), XO ( n = 8), other SCA ( n = 7), and triploidy/VT were 94%, 100%, 58.3%, 66.7%, 70%, and 57.1%, respectively. None of repeated no‐calls had aneuploidies. Conclusion: SNP‐based NIPS has high PPVs for T21 and T18. Although the proprietary SNPs library is not population‐specific, uninformative SNPs are uncommon. Abstract : Single‐nucleotide polymorphism (SNP)‐based noninvasive prenatal screening has high positive predictive values for trisomy 21 and 18. Although the proprietary SNPs library is not population‐specific, uninformative SNPs are uncommon.